PENERAPAN APLIKASI KOPERASI PINTAR (KOPPI) SEBAGAI INOVASI LAYANAN KOPERASI PADA PT. WILMAR GROUP BERBASIS ANDROID - Sandi Fadilah; Leony Nurtria Effendi; Lulu Khairunisa; Ranti Rahmadhani (Komunitas Manajemen Kompetitif, 2025)
Digital transformation has become an urgent necessity for cooperatives to improve operational efficiency and service quality in the modern era. Koperasi Bersama Wilmar Group, Dumai City, previously still used a manual system that caused delays in processes, lack of data accuracy, and low member satisfaction. This research aims to develop and implement an Android-based digital cooperative application to address these issues and support the modernization of cooperative services. The research method used is a case study with a combined quantitative and qualitative approach. Data collection was conducted through direct observation of the cooperative service process and analysis of member loan and savings transaction data that had previously been recorded manually. The application system was developed using PHP technology with the Laravel Framework as the service, ReactJS as the admin panel for the management, and Flutter for the Android application. It also uses a MySQL database. The results of qualitative testing show an increase in members' positive perception towards easier service access, information transparency, and a faster loan application process. Quantitatively, there was an increase in efficiency in the number of transactions and service processing time, as shown by the comparison of transaction data from January to April 2025. The Black Box Testing method is used to ensure that all application features function properly. This research recommends continuous development of the application system, regular training for members and administrators, as well as periodic evaluation of the need for new features so that the digital transformation of cooperatives can be sustainable and responsive to the needs of members in the future